Tectonic evolution of the eastern margin of the Tibetan plateau: Insight from crustal structures using P wave receiver functions. (15th April 2020) - Tian, Muyu; Huang, Zhouchuan; Wang, Liangshu; Xu, Mingjie; Mi, Ning; Yu, Dayong; Wang, Haibo; Gou, Tao; Xu, Mijian; Han, Cunri; Hao, Shijie; Bi, Yajing
Graphical abstract: Highlights: We study crustal thickness and velocities in the eastern margin of the Tibetan plateau. There is a significant Moho step beneath the Longmenshan fault zone. Low velocity anomalies are notable in the mid-lower crust beneath the plateau. Ancient deformation is clear in the crust beneath the Sichuan Basin. Abstract: The eastern margin of the Tibetan plateau is under ongoing expansion. Rise and growth of the Longmenshan are results of the interaction between the Songpan-Ganzi Terrane and the Sichuan Basin. In order to understand the block interactions in the eastern plateau margin, we studied the crustal structures using P wave receiver functions (including H-k staking, CCP stacking, and velocity inversion) with the waveforms recorded by 115 portable stations. The Moho, indicated by clear Ps phases, is generally deeper in the Songpan-Ganzi Terrane than in the Sichuan Basin, while a step is notable under the Longmenshan fault zone. We found a low velocity anomaly in the mid-lower crust below the Songpan-Ganzi Terrane and Longmenshan fault zone, which may imply the accumulated partial melting materials in the deep crust under the eastern plateau margin. Clear P-to-s converted phases are found within the crust of the Sichuan Basin. They look as apparent huge anticline structures, which may be caused by ancient crustal deformation under the stable craton.